TEACHING VISUAL ARTS IN GRADES 5–7 USING A TIERED STEP-BY-STEP APPROACH - Boboqulov Javohir Hamzayevich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article explores the implementation of a tiered, step-by-step approach in teaching visual arts to students in grades 5–7. The study emphasizes the importance of structuring lessons in progressive stages, allowing learners to develop artistic skills systematically while enhancing creativity, observation, and aesthetic understanding. By moving from basic exercises to more complex compositions, students gain confidence in their abilities and cultivate both technical proficiency and expressive competence. The tiered approach also integrates modern pedagogical strategies, including project-based learning, interactive activities, and digital tools, to engage students effectively. This method supports the development of visual literacy, critical thinking, and problem-solving, while fostering a deeper appreciation of art and cultural heritage.